The role of transcatheter arterial chemoinfusion (TACI) in unresectable adenocarcinoma colorectal:a case report - Bagaswoto Poedjomartono; P Pramiadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Colorectal cancer (CRC) is the fourth most common cancer in worldwide. In the last 10 years, the mortality rate of CRC decreased by more than 20% and 5-year survival remains approximately 60% due to the rising developments in diagnostic techniques and optimization of surgical, neoadjuvant and palliative therapies. We reported a case of 80-year-old woman with diarrhea, blood in the stool and weight loss for a year. The patient was diagnosed with colonic polyp eight years ago. In double-contrast barium enema (DCBE) showed filling defects in sigmoid with pedunculated form. Optical colonoscopy demonstrated tumor in sigmoid. Computed tomography (CT) abdomen showed circumferential thickening and luminal narrowing of sigmoid colon with stranding of the serosa and mesenteric fat as well as enlarge pericolic nodes without distant metastasis. Based on American Joint Committee on Cancer criteria the stage was T3N1M0. From histopathological diagnosis, the tumor was well differentiated adenocarcinoma. We concluded as unresectable adenocarcinoma colorectal. Patient received transcatheter arterial chemoinfusion (TACI) with oxaliplatin and bevacizunab in three courses every 2 months. After first TACI, symptoms and patient’s performance status improved without systemic side effects. Arteriography imaging showed decrease in tumor staining after third TACI. CT evaluation showed a significant decrease of tumor size, without nodal and distant metastasis.In this case, TACI treatment with oxaliplatin and bevacizumab in unresectable adenocarcinoma colorectaldemonstrated improvement of patient’s performance status, partial response, decrease stage and symptoms, without systemic side effects. It is proven that TACI treatment may be an effective palliative therapy for unresectable colorectal cancer. Further studies should be performed to verify these findings.We reported a case of a woman with unresectable adenocarcinoma colorectal showed good results after received TACI treatment.